2017
DOI: 10.1101/206110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced Astrocyte Responses are Driven by a Genetic Risk Allele Associated with Multiple Sclerosis

Abstract: Epigenetic annotation studies of genetic risk variants for multiple sclerosis (MS) implicate dysfunctional lymphocytes in MS susceptibility; however, the role of central nervous system (CNS) cells remains unclear. We investigated the effect of the risk variant, rs7665090 G , located near NFKB1, on astrocytes. We demonstrated that chromatin is accessible at the risk locus, a prerequisite for its impact on astroglial function. The risk variant was associated with increased NF-κB signaling and target gene express… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…During acute demyelination in MS, progressive multifocal leukoencephalopathy, metachromatic leukodystrophy, and subacute infarction, astrocytes remove myelin via receptor‐mediated endocytosis, which results in activation of the transcription factor NF‐κB and further release of chemokines (Ponath et al, ). An astrocytic risk variant associated with increased NF‐κB activation has also been identified, and drives lymphocyte recruitment with increasing lesion size, contributing to local autoimmune inflammation (Brambilla et al, ; Ponath et al, ). In Alzheimer's disease, plaque‐associated astrocytes may become activated and eliminate Aβ, but it is unclear if this is a protective mechanism or contributes to pathogenesis and secondary plaque formation (Garwood et al, ; Nagele et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During acute demyelination in MS, progressive multifocal leukoencephalopathy, metachromatic leukodystrophy, and subacute infarction, astrocytes remove myelin via receptor‐mediated endocytosis, which results in activation of the transcription factor NF‐κB and further release of chemokines (Ponath et al, ). An astrocytic risk variant associated with increased NF‐κB activation has also been identified, and drives lymphocyte recruitment with increasing lesion size, contributing to local autoimmune inflammation (Brambilla et al, ; Ponath et al, ). In Alzheimer's disease, plaque‐associated astrocytes may become activated and eliminate Aβ, but it is unclear if this is a protective mechanism or contributes to pathogenesis and secondary plaque formation (Garwood et al, ; Nagele et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know this is the most comprehensive study analyzing genotypes in relation to MS pathological characteristics. Our results illustrate that extensive and quantitative pathological characterization of autopsy tissue in sufficient numbers of MS brain donors enables the translation of genotypic variation with known effects on clinical outcome into pathological mechanisms, for example lesion activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this NF-κB-relevant risk variant promotes pro-inflammatory changes in astrocytes that might help target aberrant immune responses to the CNS. This challenges the view that MS is mediated solely through dysregulation of lymphocytes and highlights the importance of astroglial NF-κB signaling for lesion formation ( 81 ) (Figure 2 ).…”
Section: Signaling Pathways In Astrocytesmentioning
confidence: 93%
“…We have recently shown that an MS risk variant, rs7665090, which increases NF-κB signaling in lymphocytes ( 123 ), substantially affects astrocyte reactivity in cell culture and MS white matter lesions ( 81 ). Astrocytes derived from induced pluripotent stem cells, obtained from MS patients carrying the risk variant, showed increased NF-κB activation, chemokine and cell adhesion molecule expression, as well as impaired glutamate uptake and reduced lactate release.…”
Section: Signaling Pathways In Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation